Volatile compounds of essential oil Centaurea behen L. grown in Iran - Esmaeili, Akbar; Khodadadi, Elham (Archives of Advances in Biosciences, 2012)
The essential oils from Compositae specie of Iran:Centaurea behen L. obtained by hydrodistillation was analyzed by GC and GC/MS. β-Caryooyllane (24.5%), β-selinene (13.9%) and valencene (11.7%) were the main components among the sixteen constituents characterized in the oil of Centaurea behen representing 93.7% of the total components detected.